Perceived success of hybrid microorganisations in a contested category - Bicho, M.; Nikolaeva, R.; Ferreira, F.; Lages, C. (Journal of Small Business Management, 2022)
The organizational literature privileges objective performance indicators often selected by researchers. There is scarce research focusing on legitimacy-challenged hybrid and microorganizations and on perceived success under exigent conditions. To address this scarcity, this study, conducted among complementary and alternative medicine (CAM) microorganizations, explores success as a subjective measure originating from managers’ perceptions. For the purpose, it integrates cognitive mapping and multiple criteria decision analysis (MCDA) – a methodological contribution to construct a subjective-success framework that can be helpful for contested hybrid microorganizations. Seven factos emerged, of which human capital is recognized as critical, while external factors are considered unimportant.